On strongly Jordan zero-product preserving maps - Ali Reza Khoddami (Sahand Communications in Mathematical Analysis, 2016)
In this paper, we give a characterization of strongly Jordan zero-product preserving maps on normed algebras as a generalization of  Jordan zero-product preserving maps. In this direction, we give some illustrative examples to show that the notions of strongly zero-product preserving maps and strongly Jordan zero-product preserving maps are completely different. Also, we prove that the direct product and the composition of two strongly Jordan zero-product preserving maps are again  strongly Jordan zero-product preserving maps. But this fact is not the case for tensor product of them in general. Finally, we prove  that every $*-$preserving linear map from a normed $*-$algebra into a $C^*-$algebra that strongly preserves Jordan zero-products is necessarily continuous.